2006
DOI: 10.1002/hpm.826
|View full text |Cite
|
Sign up to set email alerts
|

Integration and collaboration in public health—a conceptual framework

Abstract: With the increasing differentiation of organisations involved in the pursuit of public health, there is also a growing need for inter-organisational integration. Starting from the concepts of differentiation and integration, this article is attempting a theoretical reconstruction based on published research on inter-organisational integration in public health and related welfare services. Different forms of integration are defined and related to each other in a conceptual framework, which is in itself an integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
454
0
30

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 392 publications
(496 citation statements)
references
References 37 publications
12
454
0
30
Order By: Relevance
“…According to Axelsson andBihari Axelsson (2006) andÅ hgren (2008), it is also important that an administrator integrates the employee in such way that everyone is informed about the care tasks and receives supervision to develop personal qualities if the organisation wants to succeed in its care tasks; something other studies can also confirm (Severinsson and Kamaker 1999;Fagerberg 2003). In dementia care, complex and multiple needs for differentiated care services often have to be addressed, meaning that cooperation between different departments within the health care sector is thus greatly needed (Hassan and Arnetz 2009;Hardy and Kingston 2009).…”
Section: Discussionmentioning
confidence: 99%
“…According to Axelsson andBihari Axelsson (2006) andÅ hgren (2008), it is also important that an administrator integrates the employee in such way that everyone is informed about the care tasks and receives supervision to develop personal qualities if the organisation wants to succeed in its care tasks; something other studies can also confirm (Severinsson and Kamaker 1999;Fagerberg 2003). In dementia care, complex and multiple needs for differentiated care services often have to be addressed, meaning that cooperation between different departments within the health care sector is thus greatly needed (Hassan and Arnetz 2009;Hardy and Kingston 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This correlates with an empirical evidence base (Tuckman, 1965;Axelsson and Axelsson, 2006;Tuckman and Jensen, 1977). In addition to this, the LIQH, as an improvement collaboratives network, is essentially emerging as a learning organisation (Senge and Sterman, 1992) and following Mitchell and Shortell (2000), fundamental to the fabric of LIQH's strategy was a continuous evaluation to sustain both development and the collaboration Promotion of a common culture was widely acknowledged and evident from others who saw real value in the CIHM Director's role in steering the Institute in conjunction with others.…”
Section: Key Lessons From the Literature For Liqhmentioning
confidence: 71%
“…However, impact is increasingly being realised as a result of sustained efforts into improved care (Baker, 2011a;Baker and Denis, 2011a). Studies have shown that the most successful types of inter-organisational collaborations are those where grounded and stable multidisciplinary teams have been long established and maintained over time (Axelsson and Axelsson, 2006), for example, as noted through success of integrated healthcare in Sweden (Ahgren and Axelsson, 2011). From a collaborative partnership's standpoint, managers must be willing to relinquish aspects of their territory and show more awareness and concern across organisations and society (Axelsson and Axelsson, 2009) -thus creating a greater common purpose.…”
Section: Characteristics Of High-performing Health Systemsmentioning
confidence: 99%
“…Cependant,parcequel'intégrationnevapasdesoidansuncontextecommeceluidelasanté, où les divisions intra et interdisciplinaires et intra et interorganisationnelles sont vives, plusieurs auteurssesontpenchéssurlesenjeuxquiysontliés.C'estainsiquelesétudesontexploré:1)les facteursdesuccèsoud'échecdel'intégration (ConradetShortell,1996;Fleury,2002;Friedmanet Goes, 2001;Shortell, Gillies et Anderson, 1994;Walston, Kimberly et Burns, 1996), 2)les déterminants et les facteurs de contingence, relevant les leviers fonctionnels et structurels à l'intégration (Axelsson et Axelsson, 2006;Gillies et al, 1993;Young, Parker et Charns, 2001), ou, encore, 3)les aspects relationnels (D'Amour et Oandasan, 2005;D'Amour, Tremblay et Bernier, 2007;Lamothe, 2002;. Ces études montrent bien la nécessité, imposée par l'intégration organisationnelle, de s'intéresser autant aux coordinations et aux mises en commun qu'aux différencesetmêmeauxdivergencesetauxfractionnements.…”
Section: Leprojetaucoeurduréseau Etdel'intégrationorganisationnellesounclassified